PENGARUH TINGKAT KETEBALAN PATI SAGU TERHADAP KADAR AIR PADA PROSES PENGERINGAN - Wastina Amuru; Jamaludin Jamaludin; Yus Witdarko (Musamus AE Featuring Journal, 2022)
The purpose of this study was to determine the effect of differences in the thickness of sago starch on the water content in the drying process. The research method used is an experimental method with a drying temperature treatment of 55oC, 65oC and 75oC for 10 hours. The results showed that the drying time required to reach the SNI standard water content of 13% was at 55°C at 7.5 hours, at 65°C at 7th hour, and at 75°C at 7.5 hours. 5.5th. The moisture content of sago flour after drying for 10 hours at 55°C with a thickness of 5mm, 10m, 15mm was 2.8%, 3.35% and 3.95%, respectively. At 65°C with 5mm, 10m, 15mm resistance respectively 3.78%, 3.89% and 4.73%. Whereas at 75°C with a thickness of 5mm, 10mm, 15mm each of 2.68%, 3.83% and 3.99%.